The Continuity of the Non-Priestly Narrative from Genesis to Exodus - Baden, Joel S. (Biblica, 2012)
The question of the continuity of the non-priestly narrative from the patriarchs to the exodus has been the center of much debate in recent pentateuchal scholarship. This paper presents as fully as possible, in the space allowed, one side of the argument, namely, that the non-priestly narrative is indeed continuous from Genesis through Exodus. Both methodological and textual arguments are brought in support of this claim, as well as some critiques of the alternative theory.